Association of Parkinson's disease-related pain with plasma interleukin-1, interleukin-6, interleukin-10, and tumour necrosis factor-α. (14th September 2018) - Li, Donghui; Song, Xiangsheng; Huang, Huayun; Huang, Huadong; Ye, Zanya
Highlights: We examined the relation between pain in Parkinson's disease (PD) and inflammation. We compared patients with PD with and without pain and healthy controls. We measured interleukin (IL)-1, IL-6, IL-10, and tumour necrosis factor-α. There was significant difference between patient groups in UPDRS-III and H–Y stage. There was significant difference in IL-1 between PD patients with pain and controls. Abstract: Objective: To study the association between Parkinson's disease (PD)-related pain and plasma interleukin (IL)‑1, IL‑6, IL‑10, and tumour necrosis factor (TNF)‑α levels. Methods: Sixty-seven participants were enrolled. Plasma inflammatory cytokine levels of IL-1, IL-6, IL-10, and TNF-α were measured with enzyme-linked immunosorbent assay. We additionally administered the third part of the Unified Parkinson's Disease Rating Scale (UPDRS III) and Hoehn and Yahr (H–Y) scale stage and recorded the course of the disease, the type and location of the pain, and the use of drugs. Results: The level of IL-1 was significantly higher in the PD-with-pain than in the healthy-control group (P < 0.05). There was no significant difference among groups in the other examined cytokine levels. There was a statistically significant difference between the PD-with-pain and the PD-without-pain groups in UPDRS III and H–Y stage. Additionally, the IL-1 level was significantly higher in patients who received a levodopa dosage of >250 mg than in their counterparts who received ≤250 mg, and the IL-1 level was higher in patients with an H–Y stage of >2 and UPDRS III of >27 than in their counterparts with an H–Y stage of ≤2 and UPDRS III of ≤27. The expression of TNF-α was higher in patients aged ≥70 years than in their counterparts aged <70 years. The level of IL-10 was significantly lower in the patients with an H–Y stage of >2 than in their counterparts with an H–Y stage of ≤2. Conclusion: The elevated level of IL-1 and the depressed level of IL-10 in the peripheral blood of patients with PD-related pain suggests that certain inflammatory cytokines may be implicated in the occurrence and clinical symptoms of PD-related pain.